Utilizing net traps to manage pyralid insect population in pond ecosystems: investigating seasonal abundance and their association with duckweeds (Journal of Biodiversity Conservation and Bioresource Management, 2023)
A one-year (May to April) study was done about the seasonal abundance of pyralid insect (Synclita occidentalis: Pyralidae), its association with the duckweed (Spirodela sp.), and the effectiveness of emergent trap as a control measure of pyralid insect in mini ponds ecosystem. The adult insects were non-feeding and selected duckweeds for oviposition and larval development. The larvae of different instars were used duckweed fronds as a trophic source (food). For this, the insect attains pest status in its larval stage. The duckweed production is highly hampered due to the attack of this pyralid insect in pond ecosystem. During experiment, two seasonal peaks were noted, one in summer and another in autumn (larvae and adults). The highest relative seasonal abundance of the adults was recorded in June (0.2) and larvae was in August (0.23). The lowest abundance of the adults and larvae was found 0.001 and 0.01, respectively during winter season. In this experiment, it was found that larvae used duckweed fronds as food in maximum 18.86 ± 0.86 and minimum 13.33 ± 0.70. The larva also built protective cases in duckweed fronds. The highest length of the larval cases was 27.07 ± 1.7 mm and width was 14.8 ± 1.75 mm. The larval feeding habit and case-making adaptability give this insect pest status. From the experiment, it was also found that the length and width of the larval cases greatly varied in different seasons and not positively correlated (P > 0.005). The total seasonal abundance of larval cases was lower in treatment ponds (54) than control (103); and not varied significantly (P > 0.005) between the experimental ponds. In addition, the net trap of adult’s emergent had an important role in suppressing pyralid pest population especially in summer. This situation indicated that it might be a key contribution as a control planning during the peak season of pyralid pest outbreak for the management of duckweed in aquatic ecosystems.Biodivers. Conserv. Bioresour. Manag. 2023, 9(2): 99-108